Diagnosis and treatment of primary CNS lymphoma in immunocompetent patients: guidelines from the European Association for Neuro-Oncology. Issue 7 (July 2015) - Hoang-Xuan, Khê; Bessell, Eric; Bromberg, Jacoline; Hottinger, Andreas F; Preusser, Matthias; Rudà, Roberta; Schlegel, Uwe; Siegal, Tali; Soussain, Carole; Abacioglu, Ufuk; Cassoux, Nathalie; Deckert, Martina; et al.
<x xml:space="preserve">Abstract</x> Summary The management of primary CNS lymphoma is one of the most controversial topics in neuro-oncology because of the complexity of the disease and the very few controlled studies available. In 2013, the European Association of Neuro-Oncology created a multidisciplinary task force to establish evidence-based guidelines for immunocompetent adults with primary CNS lymphoma. In this Review, we present these guidelines, which provide consensus considerations and recommendations for diagnosis, assessment, staging, and treatment of primary CNS lymphoma. Specifically, we address aspects of care related to surgery, systemic and intrathecal chemotherapy, intensive chemotherapy with autologous stem-cell transplantation, radiotherapy, intraocular manifestations, and management of elderly patients. The guidelines should aid clinicians in their daily practice and decision making, and serve as a basis for future investigations in neuro-oncology.